A question of standing the history of the CIA - Rhodri Jeffreys-Jones (Oxford University Press New York, 2022)
"This book presents an overview of the Central Intelligence Agency''s (CIA's) origins, successes, and failures, and looks at key events, such as the Bay of Pigs episode. It highlights the CIA''s effectiveness, which depended on its standing and scale of impact in the White House. It also explains how the CIA''s success depended on the ability of a president to understand intelligence briefings and his willingness to heed them, which is a function of personality and political priorities. The chapter book looks at the standing of the CIA in democratic America that is discernibly dependent on public opinion. It considers the significance of the CIA''s standing abroad and affirms that its covert actions were the greatest single cause of anti-Americanism in the post-World War II era"-- Provided by publisher
Keywords: CIA